Neuroplastin expression is essential for hearing and hair cell PMCA expression - Xiao Lin; Michael G. K. Brunk; Pingan Yuanxiang; Andrew W. Curran; Enqi Zhang; Franziska Stöber; Jürgen Goldschmidt; Eckart D. Gundelfinger; Maike Vollmer; Max F. K. Happel; Rodrigo Herrera-Molina; Dirk Montag (Brain Structure and Function, 2021)
Hearing deficits impact on the communication with the external world and severely compromise perception of the surrounding. Deafness can be caused by particular mutations in the neuroplastin ( Nptn ) gene, which encodes a transmembrane recognition molecule of the immunoglobulin (Ig) superfamily and plasma membrane Calcium ATPase (PMCA) accessory subunit. This study investigates whether the complete absence of neuroplastin or the loss of neuroplastin in the adult after normal development lead to hearing impairment in mice analyzed by behavioral, electrophysiological, and in vivo imaging measurements. Auditory brainstem recordings from adult neuroplastin-deficient mice ( Nptn −/− ) show that these mice are deaf. With age, hair cells and spiral ganglion cells degenerate in Nptn −/− mice. Adult Nptn −/− mice fail to behaviorally respond to white noise and show reduced baseline blood flow in the auditory cortex (AC) as revealed by single-photon emission computed tomography (SPECT). In adult Nptn −/− mice, tone-evoked cortical activity was not detectable within the primary auditory field (A1) of the AC, although we observed non-persistent tone-like evoked activities in electrophysiological recordings of some young Nptn −/− mice. Conditional ablation of neuroplastin in Nptn lox/loxEmx1Cre mice reveals that behavioral responses to simple tones or white noise do not require neuroplastin expression by central glutamatergic neurons. Loss of neuroplastin from hair cells in adult Nptn Δlox/loxPrCreERT mice after normal development is correlated with increased hearing thresholds and only high prepulse intensities result in effective prepulse inhibition (PPI) of the startle response. Furthermore, we show that neuroplastin is required for the expression of PMCA 2 in outer hair cells. This suggests that altered Ca 2+ homeostasis underlies the observed hearing impairments and leads to hair cell degeneration. Our results underline the importance of neuroplastin for the development and the maintenance of the auditory system.

Brain structural concomitants of resting state heart rate variability in the young and old: evidence from two independent samples - Hyun Joo Yoo; Julian F. Thayer; Steven Greening; Tae-Ho Lee; Allison Ponzio; Jungwon Min; Michiko Sakaki; Lin Nga; Mara Mather; Julian Koenig (Brain Structure and Function, 2018)

Hippocampal size is related to short-term true and false memory, and right fusiform size is related to long-term true and false memory - Bi Zhu; Chuansheng Chen; Elizabeth F. Loftus; Qinghua He; Xuemei Lei; Qi Dong; Chongde Lin (Brain Structure and Function, 2016)